Profiling of Human Circulating Dendritic Cells and Monocyte Subsets Discriminates Between Type and Mucosal Status in Patients With Inflammatory Bowel Disease. Issue 2 (17th June 2020) - Ortega Moreno, Lorena; Fernández-Tomé, Samuel; Chaparro, María; Marin, Alicia C; Mora-Gutiérrez, Irene; Santander, Cecilio; Baldan-Martin, Montserrat; Gisbert, Javier P; Bernardo, David
Abstract: Background: Intestinal dendritic cells (DC) and macrophages drive disease progression in patients with inflammatory bowel disease (IBD). We aimed to characterize the activation and homing profile of human circulating DC and monocyte subsets in healthy control patients (CP) and IBD patients. Methods: Eighteen CP and 64 patients with IBD were categorized by diagnoses of Crohn disease (CD) and ulcerative colitis (UC), either endoscopically active (inflamed) or quiescent. Circulating type 1 conventional DC, type 2 conventional DC, plasmacytoid DC, classical monocytes, nonclassical monocytes, and intermediate monocytes were identified by flow cytometry in each individual and characterized for the expression of 18 markers. Association between DC/monocytes and IBD risk was tested by logistic regression. Discriminant canonical analyses were performed to classify the patients in their own endoscopy category considering all markers on each subset. Results: CCRL1, CCR3, and CCR5 expression on circulating type 1 DC; CCRL1 expression on nonclassical monocytes; and CCR9 and β7 expression on classical monocytes allowed us to discriminate among the different study groups. Indeed, the same markers (excluding β7) were also associated with IBD when all DC and monocyte subsets were considered at the same time. Conclusions: Monitoring the phenotype of human circulating DC and monocyte subsets may provide novel tools as biomarkers for disease diagnosis (CD/UC) or mucosal status (inflamed/noninflamed) in the absence of an invasive colonoscopy.